Histological and immunohistochemical characterization of the Mongolian gerbil's mammary gland during gestation, lactation and involution - Leonel, Ellen C.R. [UNESP]; Falleiros, Luiz R. [UNESP]; Campos, Silvana G.P. [UNESP]; Taboga, Sebastião R. [UNESP] (Elsevier, 2017)
The morphological description of normal tissues is fundamental for making comparisons and in order to identify injuries and lesions. The aim of this work was to describe the morphological characteristics of the female Mongolian gerbil's (Meriones unguiculatus) normal mammary gland, the average expression of hormone receptors, and the average proliferation rates in the epithelial cells during the periods of lactation, pregnancy and involution. Dams were euthanized on the 14th and 21st gestational days, 7 and 14 days after parturition, and 3 and 5 days after weaning. The dams’ mammary tissues were processed and were submitted to haematoxylin and eosin staining, Periodic Acid Schiff (PAS) staining, and Gomori's Reticulin staining. Additionally, immunohistochemistry was performed for the characterization of myoepithelial cells with α-actin, the proliferation rates with proliferating cell nuclear antigen (PCNA), the estrogen hormonal receptors (ESR1 and ESR2), and progesterone receptor (PR) quantifications. It was observed that the abundant adipose tissues were replaced by glandular epithelia and there was an increase in the epithelial cell's height (from 5.97 to 32.4 μm in 14th and 21st gestational days and from 20.64 to 25.4 μm in 7th and 14th lactational days, respectively) and the acini diameters (from 24.88 to 69.92 μm in 14th and 21st gestational days and from 139.69 to 118.59 μm in 7th and 14th lactational days, respectively) with the progression of gestation and lactation. The PAS staining intensity varied throughout the glands and between the stages that were evaluated. The extracellular matrix showed different phenotypes too, with more of a presence of the Type I collagen during the early gestation and involution and with more reticular fibers (Type III collagen) during the late gestation period and lactation. The myoepithelial layers showed alterations in their distribution with thick patterns as verified by the α-actin labeling. The PCNA showed higher rates of the marked cells in 14th and 21st gestational days (40.25 and 60.28%) and in 7th and 14th lactational days (64.08 and 65.08%). The hormone receptor quantifications showed a high variation in the rates: the average PR staining decreased from 14th to 21st gestational days (from 42.3 to 8.54%), from 7th to 14th lactational days (from 59.83 to 23.18%) and from 3rd to 5th days after weaning (from 39.98 to 12.72). There were higher averages of ESR1 staining in gestational days 14 and 21(from 58.06 to 30.02%). ESR2 staining decreased during gestation (25.7 and 12.94% in 14th and 21st gestational days)and involution (from 50.97 to 30.18% in 3rd and 5th days after weaning). The Mongolian gerbils showed similar morphological characteristics when they were compared to mice and rats. However, the higher proliferation rates with a smaller involution period compared to other murine characterized this species as being adequate for mammary pathologies studies.
Keywords: Cell proliferation; Gerbil; Hormonal receptor; Immunohistochemistry; Mammary epithelium; Morphology